Cymbidium brevifolium (Orchidaceae; Epidendroideae), a new species from China: evidence from morphological and molecular data - Zhou, Zhuang; Zhang, Diyang; Chen, Gui-Zhen; Yu, Xia; Li, Cheng-Ru; Lan, Si-Ren; Liu, Zhong-Jian (Phytotaxa, 2020)
A new orchid species, Cymbidium brevifolium, from Hubei Province, China, is described and illustrated based on morphological and molecular analyses. A detailed comparison between the newly discovered orchid and other members of Cymbidium was conducted. The new orchid is distinct from all other recognized species in Cymbidium. Phylogenetic analyses based on nuclear (ITS) and plastid DNA (matK and rbcL) sequence data support the status of C. brevifolium as a new species, which is sister to C. faberi.